2021
DOI: 10.2147/tacg.s262866
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predictors of Mortality in Patients with Multiple Myeloma

Abstract: Multiple myeloma (MM) is a heterogeneous disease featured by clonal plasma cell proliferation and genomic instability. The advent of next-generation sequencing allowed unraveling the complex genomic landscape of the disease. Several recurrent genomic aberrations including immunoglobulin genes translocations, copy number abnormalities, complex chromosomal events, transcriptomic and epigenomic deregulation, and mutations define various molecular subgroups with distinct outcomes. In this review, we describe the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 112 publications
2
4
1
Order By: Relevance
“…Loss of chromosome 13 remains the most prevalent event of the two, while targeted deletions are rarer in this cohort, concordant with previous studies [39]. Loss of chromosome 13 was detected in both primary genetic classes, including seven with non-hyperdiploid cases with an IGH rearrangement (samples 02, 03, 07, 12, 41, 44, 45) and five with HDM (samples 01, 30,33,38,42). Gene content within the 13q deleted region showed that the DLEU1 and DLEU2 genes were included within this region (samples 06, 24), while the RB1 gene was deleted in only one of the two cases (minimal region of deletion at 13q14.2q14.3).…”
Section: Successful Detection Of Classical Primary Abnormalities In M...supporting
confidence: 91%
See 2 more Smart Citations
“…Loss of chromosome 13 remains the most prevalent event of the two, while targeted deletions are rarer in this cohort, concordant with previous studies [39]. Loss of chromosome 13 was detected in both primary genetic classes, including seven with non-hyperdiploid cases with an IGH rearrangement (samples 02, 03, 07, 12, 41, 44, 45) and five with HDM (samples 01, 30,33,38,42). Gene content within the 13q deleted region showed that the DLEU1 and DLEU2 genes were included within this region (samples 06, 24), while the RB1 gene was deleted in only one of the two cases (minimal region of deletion at 13q14.2q14.3).…”
Section: Successful Detection Of Classical Primary Abnormalities In M...supporting
confidence: 91%
“…We also identified two cases of t(4;14) (sample 07 and 45; 10%) and a single case of t(6;14) (sample 12), t(14;16) (sample 02) and t(14;20) (sample 44) (Figure 1c-f and Figure S3). While a high frequency (~15%) of IGH translocations involving loci other than the canonical partners (e.g., TXNDC5, B2M, JUND, JUN) is reported in the literature [9,30], such abnormalities were not identified in this small cohort. However, we did uncover two variant translocations (t(14;16;8;8) and t(11;14;19)), both involving at least three translocation partners.…”
Section: Successful Detection Of Classical Primary Abnormalities In M...contrasting
confidence: 65%
See 1 more Smart Citation
“…Multiple myeloma (MM) is a haematologic malignancy characterized by abnormal proliferation of clonal plasma cells. 1 MM is a heterogeneous disease and, while early stages are asymptomatic, progression lowers resistance to infection; causes skeletal damage; and leads to hypercalcaemia, renal failure, anaemia and osteolytic lesions. 2,3 While standard of care has evolved and has offered improvements in overall survival, the majority of MM patients will eventually fail to respond to current treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a haematologic malignancy characterized by abnormal proliferation of clonal plasma cells 1 . MM is a heterogeneous disease and, while early stages are asymptomatic, progression lowers resistance to infection; causes skeletal damage; and leads to hypercalcaemia, renal failure, anaemia and osteolytic lesions 2,3 .…”
Section: Introductionmentioning
confidence: 99%